STATISTICAL LITERACY KNOWLEDGE DIFFUSION: DIDACTICAL TRANSPOSITION FROM SCHOLARLY KNOWLEDGE TO KNOWLEDGE TO BE TAUGHT ON LINEAR REGRESSION - Palupi Sri Wijayanti; Didi Suryadi; Dadan Dasari; Al Jupri (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study examines the process of external didactic transposition in linear regression material, namely the transformation of scholarly knowledge into knowledge to be taught. This transposition is important to ensure that knowledge that is complex and tends to be abstract for students can be accessed and easily understood, especially in the context of linear regression so that it can develop students' statistical literacy. The research method was conducted with a document study by analysing primary books on statistics, reference guidelines for the preparation of mathematics textbooks, and educational curriculum documents in Indonesia. The results of the study showed that the knowledge adaptations that have been identified are the meaning of dependent and independent variables, the concept of linear regression, the concept of best fit line, linear regression equation model, and random error. Although there are knowledge adaptations that facilitate understanding for students, there are also limitations in the presentation of random error distribution assumptions in the knowledge to be taught. The contribution of this research is an understanding of the construction of statistical knowledge presented in the educational context and the strengthening of materials that can develop students' statistical literacy. Penelitian ini mengkaji proses transposisi didaktis eksternal pada materi regresi linear, yaitu transformasi pengetahuan ilmiah (scholarly knowledge) menjadi pengetahuan yang akan diajarkan (knowledge to be taught). Transposisi ini penting untuk memastikan pengetahuan yang kompleks dan cenderung abstrak bagi siswa dapat diakses dan mudah dipahami, khususnya dalam konteks regresi linear sehinga dapat mengembangkan literasi statistik siswa. Metode penelitian dilakukan dengan studi dokumen melalui analisis buku primer materi statistika, pedoman acuan penyusunan buku teks matematika, dan dokumen kurikulum pendidikan di Indonesia. Hasil studi menunjukkan adaptasi pengetahuan yang telah teridentifikasi yaitu pemaknaan variabel dependen dan independen, konsep regresi linear, konsep garis best fit, model persamaan regresi linear, serta random error. Walaupun terdapat adaptasi pengetahuan yang memfasilitasi pemahaman untuk siswa, tetapi ditemukan pula adanya keterbatasan dalam penyajian asumsi distribusi random eror dalam knowledge to be taught. Kontribusi penelitian ini yaitu pemahaman terhadap konstruksi pengetahuan statistika yang disajikan pada konteks pendidikan serta penguatan materi yang dapat mengembangkan literasi statistik siswa.